Analisis Penerapan Metode Role Playing Materi Drama untuk Meningkatkan Motivasi Belajar Siswa Kelas VIII SMPN 7 Mataram - Mustamiin, M. Zainal (YASIN, 2022)
Student learning motivation is one of the goals in the learning process so that students are motivated to receive lessons, in other subjects including Indonesian it is necessary to apply appropriate methods or strategies so that students are motivated in the learning process. The main objective of this study was to determine the impact of applying the role playing method to drama material for Indonesian language subjects for class VIII SMPN 7 Mataram. This research is a Pre-Experimental design with the type of One Group Pretest and Posttest design, namely only one class is given treatment and then analyzes the results. Based on the results of the final recapitulation of the pretest value, it can be interpreted that there was an increase in motivation from before being given treatment and after being given treatment, by looking at the average value, the posttest value obtained an average value of 58.9 which is in the medium category, and the posttest results obtained the average value of 73 is in the high category. This means that the application of the role playing method to drama material for Indonesian language subjects can increase student learning motivation.